The Effect of Picture Media on Mastery of Vocabulary At Grade VII Student - Dian Melati Siagian; Siska Situmeang; Entika Cintami Siahaan; Sindy Gloria Nainggolan; Evi Roseria Sitinjak (Departement of Mathematics Education, 2023)
Picture Series is one of the media images that can be used to support and help vocabulary learning. Vocabulary is very important for everyone to learn especially a students, because if someone has mastery of vocabulary in English then when he/she uses English, he/she will have no difficulties. The aims of this study was to find out whether picture series had a good impact on improving and developing students' mastery of vocabulary or not. In this study, researchers used a quantitative experimental method. Based on the results of the research conducted by the researcher, it was found that picture series had a significant impact on students' mastery of vocabulary.